Ekranisasi Novel Bumi Manusia karya Pramoedya Ananta Toer ke Film “Bumi Manusia” karya Sutradara Hanung Bramantyo - Andani, Puti Ria; Pangesti, Nesa Riska (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2024)
The phenomenon of novels being filmed is now a trend in the Indonesian film world, raising readers' curiosity about whether the adapted film will be the same as the content of the novel. This study aims to describe the form of reduction, addition, and change of variation in the ecranization process of the novel Bumi Manusia by Pramoedya Ananta Toer into the film “Bumi Manusia” by Hanung Bramantyo, as well as the background of these changes. The research method used is descriptive qualitative with Eneste's ecranization theory. The research data are in the form of dialogues, monologues, and narratives in the novel and visualization of the film “Bumi Manusia”. The results of this study are: (1) aspects of reduction in character and characterization elements were found as many as 6 reductions, 72 reductions in plot elements, and 15 reductions in setting elements; (2) aspects of additions to character and characterization elements were found as many as 8 additions, 23 additions to plot elements, and 3 additions to setting elements; (3) aspects of changes in variation in character and characterization elements were found as many as 7 changes in variation, 41 changes in variation in plot elements, and 21 changes in variation in setting elements. The ecranization process that occurred was not only influenced by the limitations of duration and production costs but also by differences in interpretation between the novelist and the director.